Strategic reading program to develop critical-creative thinking in high school students - Muñoz, César (2022)
The objective was to design a program of reading strategies to develop critical and creative thinking (PCC) in the students of the VI cycle of the educational institution Diego Ferré Sosa de Monsefú. The research was of a primary propositional type, in which 137 students participated, who were administered a questionnaire on the development of critical and creative thinking, elaborated separately for every kind of thought and covering the dimensions of each one of them. The instruments were duly validated and with a reliability coefficient of 0.80. The results regarding the level of development of critical and creative thinking indicate that 45.99% of the total sample are at the medium level for critical thinking, and 51.09% are also at the medium level concerning creative thinking, which makes it possible to determine that almost half of the students surveyed need to reorient the development of higher-order thinking skills that allow them to strengthen their cognitive abilities.